2021
DOI: 10.1111/ijlh.13533
|View full text |Cite
|
Sign up to set email alerts
|

Early hematological indicators of severe COVID‐19 disease in hospitalized patients: Data from a South Asian population

Abstract: Introduction Outbreak of corona virus disease in 2019 (COVID‐19) has resulted in significant morbidity and mortality worldwide. Our aim is to document hematological parameters of patients with COVID‐19 during initial stage of diagnosis and to identify early hematological indicators of severe infection. Materials and methods This retrospective study was conducted at Shifa International Hospital, Pakistan from April to November 2020. Patients hospitalized with COVID‐19, diagnosed on RT‐PCR and had a complete blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…SARS‐CoV‐2 induced cytokines release, direct virus‐induced myelocytotoxicity, and overproduction of marrow in response to stress/inflammation causing mobilization of marrow reserves in the peripheral blood circulation are a few hypotheses explaining the reason for granulocytic left shift akin to bacterial infections in severe cases. Sharif et al, in their study, reported that neutrophilic leucocytosis was significantly associated with the development of acute respiratory distress syndrome, mortality, and need for a ventilator 24 . Most of the deceased patients in the current study showed significant leucocytosis with marked neutrophilia and toxic granulation as compared to survivors, indicating that these patients might have a secondary bacterial infection as an underlying cause of death.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…SARS‐CoV‐2 induced cytokines release, direct virus‐induced myelocytotoxicity, and overproduction of marrow in response to stress/inflammation causing mobilization of marrow reserves in the peripheral blood circulation are a few hypotheses explaining the reason for granulocytic left shift akin to bacterial infections in severe cases. Sharif et al, in their study, reported that neutrophilic leucocytosis was significantly associated with the development of acute respiratory distress syndrome, mortality, and need for a ventilator 24 . Most of the deceased patients in the current study showed significant leucocytosis with marked neutrophilia and toxic granulation as compared to survivors, indicating that these patients might have a secondary bacterial infection as an underlying cause of death.…”
Section: Discussionmentioning
confidence: 44%
“…Sharif et al, in their study, reported that neutrophilic leucocytosis was significantly associated with the development of acute respiratory distress syndrome, mortality, and need for a ventilator. 24 Most of the deceased patients in the current study showed significant leucocytosis with marked neutrophilia and toxic granulation as compared to survivors, indicating that these patients might have a secondary bacterial infection as an underlying cause of death.…”
Section: Discussionmentioning
confidence: 56%
“…Sample size was calculated using WHO calculator. 8 Informed consent about the sampling and research was taken from patients or their families.…”
Section: Methodsmentioning
confidence: 99%
“…7 Commonly affected parameters include platelet count, absolute lymphocyte count, neutrophil count, NLR ratio and D dimers. 8 We carried out this study to determine hematological, coagulation and inflammatory markers in hospitalized PCR positive covid patients which can be used as a monitoring tool and give an idea about disease severity as well. Furthermore, these parameters can also give us an idea where PCR facility is not available so the suspected patients may be timely isolated, referred and managed at the desired facility.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, lymphopenia is one of the laboratory markers of the SARS-CoV-2 infection and has been considered a poor prognostic factor regarding the severity of the COVID-19 disease 7 , 8 .…”
Section: Introductionmentioning
confidence: 99%